Mediating empathy: The role of news consumption in mitigating attitudes about race and immigration. (June 2019) - Kaufhold, Kelly
Controversies over racism and xenophobia during and after the campaign of President Donald Trump contributed to big increases in media consumption—and racist incidents. This study examines whether and how much news media consumption mitigates perceptions of 12 measures of attitudes about race and immigration, using a national instrument of 64, 600 cases. Selective exposure played an outsized role in media consumption during this election cycle and was highly predictive of partisan attitudes, which predicted attitudes on race and immigration. News media use—especially newspaper use—does soften attitudes about race and immigration, although it is not as predictive as party identification.